Comparative cost‐effectiveness of neoadjuvant chemotherapy regimens for muscle‐invasive bladder cancer: Results according to VESPER data. Issue 24 (17th October 2022) - Joyce, Daniel D.; Wymer, Kevin M.; Sharma, Vidit; Moriarty, James P.; Borah, Bijan J.; Geynisman, Daniel M.; Plimack, Elizabeth R.; Costello, Brian A.; Pagliaro, Lance C.; Boorjian, Stephen A.
Abstract: Background: The VESPER trial demonstrated improved progression‐free (PFS) and (preliminarily) overall survival (OS) with six cycles of neoadjuvant dose‐dense methotrexate, vinblastine, doxorubicin, and cisplatin (ddMVACx6) versus four cycles of gemcitabine and cisplatin (GCx4) before radical cystectomy (RC) for muscle‐invasive bladder cancer (MIBC), but with increased toxicity. This study compares the cost‐effectiveness of these regimens. Methods: A cost‐effectiveness analysis of neoadjuvant ddMVACx6 and GCx4 was performed using a decision‐analytic Markov model with 5‐year, 10‐year, and lifetime horizons. Probabilities were derived from reported VESPER data. Utility values were obtained from the literature. Primary outcomes were effectiveness measured in quality‐adjusted life years (QALY) and incremental cost‐effectiveness ratio (ICER) with a willingness to pay threshold of $100, 000 per QALY. One‐way and probabilistic sensitivity analyses were performed to evaluate the robustness of the model. Results: At 5 years, ddMVACx6 improved QALYs by 0.30 at an additional cost of $16, 100, rendering it cost‐effective relative to GCx4 (ICER: $53, 284/QALY). Additionally, probabilistic sensitivity analysis found ddMVACx6 to be cost‐effective in 79% and 81% of microsimulations at10‐year and lifetime horizons, respectively. One‐way sensitivity analysis demonstrated a minimum difference in 5‐year progression of 0.9% and progression mortality of 0.7% between ddMVACx6 and GCx4 was necessary for ddMVACx6 to remain cost‐effective. Conclusions: Neoadjuvant ddMVACx6 was more cost‐effective than GCx4 for MIBC. These data, together with the improved PFS and (albeit preliminary) OS noted in VESPER, support use of this regimen in appropriate candidates for neoadjuvant chemotherapy before RC. Lay summary: We performed a benefit‐to‐cost analysis using evidence from a randomized controlled trial that compared two different chemotherapy treatments before bladder removal for bladder cancer that had invaded into the bladder muscle. Despite being more expensive and having a greater likelihood of toxicity, six cycles of dose‐dense methotrexate, vinblastine, doxorubicin, and cisplatin was more cost‐effective (or had higher value) than four cycles of gemcitabine and cisplatin. Abstract : Using a Markov model based on VESPER trial data, six cycles of neoadjuvant dose‐dense methotrexate, vinblastine, doxorubicin, and cisplatin was found to be more cost‐effective than four cycles of gemcitabine and cisplatin for patients with muscle‐invasive bladder cancer at 5‐year, 10‐year, and lifetime horizons. These findings support preferential use of dose‐dense methotrexate, vinblastine, doxorubicin, and cisplatin in appropriate candidates for neoadjuvant chemotherapy before radical cystectomy.